The Prevalence, Location, and Dimensions Of Interthalamic Adhesions and Their Clinical Significance: Corpse Brain Analysis - Patra, Apurba; Ravi, Kumar Satish; Asghar, Adil (Asian Journal of Neurosurgery, 2022)
Background Interthalamic adhesion (ITA) or massa intermedia is a midline rod-like neural structure interconnecting the medial surfaces of two thalami. Its absence is considered as a midline defect associated with schizophrenia spectrum disorder. The present study aimed to determine the prevalence, location, and dimensions of the ITA in South Asian brains.Materials and Methods One hundred midsagittal sections of adult cadaveric brains were examined for the presence or absence of ITAs, their location about the lateral wall of the third ventricle, and their dimensions.Results ITA was found in 86 sections. In two cases, it was double. There was no significant relationship between the incidence of ITAs and sex (p > 0.05). The ITA was most commonly located in the anterosuperior quadrant. The horizontal diameter was 4.61 ± 1.17 mm, and the vertical diameter was 3.10 ± 0.78 mm. In all cases, the horizontal diameter was longer than the vertical. The average area of the ITA was significantly larger in females (17.56 ± 5.26 mm2) than in males (13.62 ± 5.22 mm2) (p = 0.025).Conclusion Presence of ITA is common in South Asian brains, with usual location in the anterosuperior quadrant of the lateral wall of the third ventricle. The cross-sectional area of the ITA was significantly larger in females than in males. No correlation was found between the surface area of the ITA and the length of the third ventricle.
Keywords: massa intermedia; neurosurgery; schizophrenia; thalamus; third ventricle